Inappropriate Medication in a National Sample of US Elderly Patients Receiving Home Health Care - Bao, Yuhua (Springer-Verlag, 2011)
BACKGROUND: With substantial morbidity and functional impairment, older patients receiving home health care are especially susceptible to the adverse effects of unsafe or ineffective medications. Home health agencies’ medication review and reconciliation services, however, provide an added mechanism of medication safety that could offset this risk. OBJECTIVE: To estimate the prevalence of potentially inappropriate medications (PIMs) among current elderly home health patients in the US. DESIGN: Cross-sectional analysis using data from the 2007 National Home and Hospice Care Survey. SUBJECTS: 3,124 home health patients 65 years of age or older on at least one medication. MAIN MEASURES: Prevalence and classification of PIM use and the association between PIM use and patient and home health agency characteristics. KEY RESULTS: In 2007, 38% (95% CI: 36–41) of elderly home health patients were taking at least one PIM. Polypharmacy was associated with an increased risk of PIM use; admission to home health care from a nursing home or other sub-acute facility (compared to admission from the community) and a payment source other than Medicare or Medicaid were associated with a decreased risk of PIM use. CONCLUSIONS: The prevalence of PIM use in older home health patients is high despite potential mechanisms for improved safety. Policies to improve the review and reconciliation processes within home health agencies and to improve physician-home health clinician collaboration are likely needed to lower the prevalence of PIM use in older home health patients.